Oscillatory electrocoagulation for treatment of surface water and greywater - Tomita, Masahiro; Friedler, Eran (Frontiers in Environmental Science, 2025)
Non-conventional water sources such as surface water (stormwater) and greywater have gained attention due to ever-increasing water demand and growing water scarcity. Electrocoagulation (ELC) is often used for treating these waters. Rotational and hydraulic mixing have been the conventional mixing methods for ELC, however there is no dominant design for ELC reactors. In this research, mixing in ELC was achieved by a novel wave-like sinusoidal oscillatory mixing. The electrodes in this combined treatment method have a dual function as a source of coagulant and as mixing paddles. The aim of the research was to develop and study the novel oscillatory ELC for different types of water: synthetic surface water (SSW), synthetic greywater (SGW), and real greywater (RGW). Experiments with SSW revealed the distance between the electrodes should be in the range of 0.8–1.0 cm to ascertain optimal mixing. The oscillatory ELC efficiently removed turbidity from the SSW. ELC removed 96, 91, 34, 42, and 2% of the turbidity, TP, COD, DOC, and TN from SGW. Floatation by gas bubbles generated in the process removed pollutants effectively, thus the slow mixing time could be shortened from 30 to 10 min, implying smaller volumes of mixing tanks. For RGW ELC removed 96, 47, 72, 35, and 11% of the turbidity, TP, COD, DOC, and TN respectively at pH 8. In ELC, hydrogen gas production at the cathode releases hydroxides to the solution. Aluminum ions produced at the anode, consume most of the hydroxides present in the solution to form several dissolved aluminum species. This keeps the pH of the solution relatively stable during ELC treatment (unlike CC with aluminum species). In summary, the oscillatory ELC was found to be a viable option to treat stormwater and greywater, requiring less pH adjustment, having lower footprint, less sludge production, no addition of chemical coagulants, and easy operation and maintenance over conventional chemical coagulation.